The effects of personality traits on adult labor market outcomes: Evidence from siblings - Jason M. Fletcher (Institute for the Study of Labor (IZA), 2012)
While large literatures have shown that cognitive ability and schooling increases employment and wages, an emerging literature examines the importance of so-called non-cognitive skills in producing labor market outcomes. However, this smaller literature has not typically used causal methods in estimating the results. One source of heterogeneity that may play an important role in producing both personality and other non-cognitive skills and labor market outcomes is family background, including genetic endowments. This paper is the first to use sibling differences to estimate the effects of personality on employment and wages and is also able to control for many other sources of heterogeneity, including attractiveness, cognitive ability, schooling, occupation, and other factors. Overall, the findings suggest that personality measures are important determinants of labor market outcomes in adulthood and that the results vary considerably by demographic group. The findings also highlight the potential role of extraversion in leading to favorable labor market outcomes, which has not been documented in many other studies.
urn:nbn:de:101:1-201206146679
Keywords: J24; J31; 330; personality; wages; sibling fixed effects; Erwerbsverlauf; Lohn; Persönlichkeitspsychologie; USA